A modified anthrax toxin-based enzyme-linked immunospot assay reveals robust T cell responses in symptomatic and asymptomatic Ebola virus exposed individuals. - Bobby Brooke Herrera; Donald J Hamel; Philip Oshun; Rolake Akinsola; Alani S Akanmu; Charlotte A Chang; Philomena Eromon; Onikepe Folarin; Kayode T Adeyemi; Christian T Happi; Yichen Lu; Folasade Ogunsola; et al. (PLoS Neglected Tropical Diseases)
Background Ebola virus (EBOV) caused more than 11,000 deaths during the 2013-2016 epidemic in West Africa without approved vaccines or immunotherapeutics. Despite its high lethality in some individuals, EBOV infection can produce little to no symptoms in others. A better understanding of the immune responses in individuals who experienced minimally symptomatic and asymptomatic infection could aid the development of more effective vaccines and antivirals against EBOV and related filoviruses. Methodology/principle findings Between August and November 2017, blood samples were collected from 19 study participants in Lagos, Nigeria, including 3 Ebola virus disease (EVD) survivors, 10 individuals with documented close contact with symptomatic EVD patients, and 6 control healthcare workers for a cross-sectional serosurvey and T cell analysis. The Lagos samples, as well as archived serum collected from healthy individuals living in surrounding areas of the 1976 Democratic Republic of Congo (DRC) epidemic, were tested for EBOV IgG using commercial enzyme-linked immunosorbent assays (ELISAs) and Western blots. We detected antibodies in 3 out of 3 Lagos survivors and identified 2 seropositive individuals not known to have ever been infected. Of the DRC samples tested, we detected antibodies in 9 out of 71 (12.7%). To characterize the T cell responses in the Lagos samples, we developed an anthrax toxin-based enzyme-linked immunospot (ELISPOT) assay. The seropositive asymptomatic individuals had T cell responses against EBOV nucleoprotein, matrix protein, and glycoprotein 1 that were stronger in magnitude compared to the survivors. Conclusion/significance Our data provide further evidence of EBOV exposure in individuals without EVD-like illness and, for the first time, demonstrate that these individuals have T cell responses that are stronger in magnitude compared to severe cases. These findings suggest that T cell immunity may protect against severe EVD, which has important implications for vaccine development.